Exploring the Potential of Coix Seeds to Mitigate High Humidity-Induced Gut Inflammation via Microbiota and Metabolite Modulation - Zhao P; Xiao C; Xuan M; Yan S; Yu X; Li W; Han L; Wang H; Zhao J; Zhang S; Zhong X (Journal of Inflammation Research, 2025)
Peihan Zhao,1 Congyou Xiao,1 Mingyang Xuan,1 Shuxin Yan,1 Xue Yu,2 Wei Li,1 Linxiao Han,1 Hanxi Wang,1 Jingbo Zhao,1 Shujing Zhang,2 Xianggen Zhong1 1Institute of Synopsis of Golden Chamber Department, School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 2Experimental Center, School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Beijing, People’s Republic of ChinaCorrespondence: Xianggen Zhong, School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Northeast Corner of the Intersection of Yangguang South Street and Baiyang East Road, Liangxiang University Park, Fangshan District, Beijing, 102401, People’s Republic of China, Email zhongxg@bucm.edu.cn Shujing Zhang, School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Northeast Corner of the Intersection of Yangguang South Street and Baiyang East Road, Liangxiang University Park, Fangshan District, Beijing, 102401, People’s Republic of China, Email Jingshuzhang@126.comBackground: Extreme humidity exacerbates gastrointestinal disorders by disrupting gut microbiota homeostasis, compromising the intestinal barrier and triggering immune dysregulation. Coix seed (Coix lacryma-jobi L.), widely used in traditional Chinese medicine for eliminating dampness, shows promise; however, its mechanisms require further elucidation.Methods: A Coix seed decoction (CD) was administered to rats exposed to 85% relative humidity (8 h/day) for 30 days. Forty rats were randomly divided into four groups: control, high-humidity exposed, Coix seed-treated control and Coix seed-treated high-humidity. The chemical composition of the CD was characterised using ultra-high-performance liquid chromatography–mass spectrometry (LC-MS), and faecal moisture content, body weight and histopathological changes were assessed. Colonic tissues were analysed by haematoxylin–eosin staining and transmission electron microscopy for structural integrity. Gut microbiota were profiled using 16S ribosomal RNA sequencing, followed by bioinformatic analysis of diversity, differential abundance and co-occurrence networks. Untargeted metabolomics was performed using LC-MS to identify metabolic alterations, and the serum inflammatory cytokines (tumour necrosis factor alpha [TNF-α], interleukin [IL]-6, IL-17) were measured by enzyme-linked immunosorbent assay.Results: High humidity disrupts gut homeostasis in rats by inducing intestinal damage, inflammation, dysbiosis and lipid metabolic disorders. Coix seed decoction significantly alleviated these effects, restoring colonic structure, rebalancing the gut microbiota (eg increasing Erysipelatoclostridium spp. Akkermansia spp. Lactobacillus spp. and reducing Escherichia spp. Shigella spp.) and correcting sphingolipid metabolism (eg sphingomyelin, ceramide). Metabolomic and transcriptomic analyses revealed that CD suppressed immune-related pathways (eg T/B cell receptor signalling, Th1/Th2 differentiation), consistent with reduced serum levels of proinflammatory cytokines (TNF-α, IL-6, IL-17). Correlation networks highlighted interactions between key microbes and metabolites, suggesting a regulatory role for Ruminococcus spp., NK4A214_group spp. and Prevotellaceae NK3B31 spp. in the therapeutic effects of CD.Conclusion: Our findings provide experimental evidence that Coix seed mitigates high humidity-induced gut injury through microbiota remodelling, lipid metabolic regulation and immune modulation.Keywords: coix seed, humidity, metabolomics analysis, gut microbiota, 16S ribosomal ribonucleic acid sequencing